2009
DOI: 10.1002/esp.1891
|View full text |Cite
|
Sign up to set email alerts
|

Using magnetic susceptibility to assess soil degradation in the Eastern Rif, Morocco

Abstract: The soil in the Rif, Morocco, is at serious risk because increasing anthropogenic pressures are gradually transforming large natural areas into farmland. The distribution of magnetic minerals within the soil profi le can be used to assess soil development and degradation. The soils in the study area are severely eroded because of a combination of highly erodible soils, intense rainstorms and scarce vegetation cover. To sample of representative soil profi les, lithology, slope gradient and land use were conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…Moreover, the transportation of nano-particles of magnetic minerals along with clay and fine particles further contributed to the increase. These results are consistent with the finding of Sadiki et al (2009).…”
Section: Natural Forestsupporting
confidence: 96%
See 1 more Smart Citation
“…Moreover, the transportation of nano-particles of magnetic minerals along with clay and fine particles further contributed to the increase. These results are consistent with the finding of Sadiki et al (2009).…”
Section: Natural Forestsupporting
confidence: 96%
“…RUSLE under predicted denudation relative to the results obtained using the magnetism-model in the over upper slopes, but over predicted denudation in the lower slopes. Sadiki et al (2009) found that the effects of land use seemed a key factor influencing the distribution of magnetic susceptibility in the soil profiles.…”
Section: Introductionmentioning
confidence: 98%
“…The RE results are consistent with those in Table 1, showing that the larger the MS the higher the RE. SADIKI et al (2009) used the magnetic susceptibility to assess the degradation of tropical soils. Thus, studies that relate the variability of erosion with MS may contribute to the development of strategies aimed at sustainable land use.…”
Section: Resultsmentioning
confidence: 99%
“…In general, there are many factors that cause magnetic susceptibility variations (MS), such as the differences in lithology (lithogenic/geogenic), soil forming processes (pedogenesis), and anthropogenic contribution of magnetic material [2,10,13]. Saddiki et al [14] confirmed that the lithology is the main factor contributing to the magnetic susceptibility variation.…”
Section: Methodsmentioning
confidence: 99%